THE INTERACTION OF SOCIAL MOBILITY AND NATIONAL CHARACTER - Usmanova Shohsanam Shavkatovna (Web of Journals Publishing, 2024)
This article examines the relationship between national character and mobility as a basis for the rise of the nation. Social mobility, in turn, elevates the character of the nation. These processes interact to form the strong will of the nation.
Keywords: Society, social mobility, nation, character, national character, feature, ethnic group.